Histopathological tendencies, sex, age and radiological results for lung cancer in the municipality of Sinop – MT (Research, Society and Development, 2022)
Objective: To describe and improve our understanding of lung cancer epidemiology. Methodology: Retrospective, descriptive and analytic epidemiological study, analyzing histological type, sex, age and radiological results for lung cancer in the municipality of Sinop – MT during the period from 2014 to 2019. Results: 219 lesion biopsies were analyzed. 113 (51.59%) confirmed a diagnosis for lung cancer. The main histological types for the histopathology diagnosis were adenocarcinoma totaling 47 (41.59%) cases, followed by squamous cell carcinoma with 27 (23.89%) cases. Regarding sex, 52 (46.02%) lung cancer cases were found in women and 61 (53.98%) cases in men. In total, the main histological type for both sexes was adenocarcinoma. Regarding age, the predominant age range was 60-69 years with 43 cases (38.05%). In relation to characteristics of tomography imaging for lung cancer cases, nodule location was statistically significant, mainly in the right lung upper lobe, a finding observed in other sources, where the upper right lobe was found to have a greater incidence of malignancy. Conclusions: the main histological type was adenocarcinoma, with the majority of malignant lesions occurring in men, with an age range from 60 to 69 years. The most common image for cancer cases was solid lesion larger than 8 mm with irregular borders found in the right lung upper lobe.